2020
DOI: 10.3347/kjp.2020.58.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Infections of Digenetic Trematode Metacercariae in Wrestling Halfbeak, Dermogenys pusilla from Bangkok Metropolitan Region in Thailand

Abstract: This study aimed to investigate metacercarial infections in the wrestling halfbeak, <i>Dermogenys pusilla</i>, collected from Bangkok metropolitan region of Thailand. A total of 4,501 fish from 78 study sites were commonly examined with muscle compression and digestion methods (only head part of fish) during September 2017 to July 2018. The overall prevalence of metacercarial infection was 86.1% (3,876/4,501 individuals), and the mean intensity was 48.9 metacercariae per fish infected. Four species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…It was reveals 58% overall prevalence of FBZP in fresh water fishes of Bhola district which are consistent with the results reported previously in the country where overall prevalence recorded 66% (Labony et al 2020). Our findings are also in agreement with the earlier findings where 86.1% prevalence of metacercariae were detected in the wrestling halfbeak, Dermogenys pusilla, collected from Bangkok metropolitan region of Thailand (Patarwut et al 2020). In our study, the MC of Clonorchis/Opisthorchis were detected from Loitta, spotted snakehead and stinging cat fish which suggests that these fishes act as the second intermediate hosts of opisthorchid flukes.…”
Section: Discussionsupporting
confidence: 92%
“…It was reveals 58% overall prevalence of FBZP in fresh water fishes of Bhola district which are consistent with the results reported previously in the country where overall prevalence recorded 66% (Labony et al 2020). Our findings are also in agreement with the earlier findings where 86.1% prevalence of metacercariae were detected in the wrestling halfbeak, Dermogenys pusilla, collected from Bangkok metropolitan region of Thailand (Patarwut et al 2020). In our study, the MC of Clonorchis/Opisthorchis were detected from Loitta, spotted snakehead and stinging cat fish which suggests that these fishes act as the second intermediate hosts of opisthorchid flukes.…”
Section: Discussionsupporting
confidence: 92%
“…With regards to the study area, Patarwut et al (2020) recently reported the infections of metacercaria-stage Posthodiplostomum sp. (diplostomatid) and Cyathocotylidae sp.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of trematode metacercariae infecting freshwater animals in Thailand have usually been performed in fish hosts (Wongsawad et al ., 2000; Mard-arhin et al ., 2001; Nithiuthai et al ., 2002; Krailas et al ., 2004, 2016; Kumchoo et al ., 2005; Pinlaor et al ., 2013; Suanyuk et al ., 2013; Namsanor et al ., 2020; Patarwut et al ., 2020; Charoensuk et al ., 2022); on the other hand, freshwater snails have occasionally been mentioned as intermediate hosts of the metacercariae (Chantima et al ., 2013, 2018; Noikong et al ., 2014; Phalee et al ., 2018; Bunchom et al ., 2020). In terms of biodiversity, the current study demonstrated a variety of metacercarial trematode larvae infecting snail intermediate hosts in Bangkok areas, as well as a variety of gastropod faunas distributed in freshwater habitats in Bangkok.…”
Section: Discussionmentioning
confidence: 99%